"We Earned the Coupon Together": The Missing Link of Experience Cocreation in Shared Coupons. (May 2023) - Fang, Eric (Er); Dong, Beibei; Zhuang, Mengzhou; Cai, Fengyan
Shared coupons, a new form of coupon, differ from coupons distributed directly from businesses (i.e., direct coupons) in that shared coupons combine two influential components: economic savings (e.g., 5 off) and social sharing (e.g., from friends). Using two lab experiments and two large-scale field experiments on social media, the authors find that regular shared coupons underperform direct coupons in terms of coupon redemption because of the norm conflict between economic incentives and communal relationships (i.e., friendships), whereas shared coupons with experience cocreation, in which coupon givers and coupon receivers must invest joint efforts to create a shared experience before redeeming the coupons, outperform direct coupons. Experience cocreation can advance social goals (e.g., building friendships), reduce the norm conflict, and thereby make customers more likely to share and to redeem coupons. The authors further investigate the effects of two strategies for driving the redemption of shared coupons with experience cocreation: changing the coupon's face value (low vs. high) and using ex post communication (social messages vs. economic messages). They find that social messages can make low-value coupons as effective as high-value coupons, thereby enabling the firm to "do more with less."